Toksisitas dan dampak empat insektisida sintetik terhadap sintasan dan perilaku makan lebah tanpa sengat Tetragonula laeviceps Smith (Hymenoptera: Apidae: Meliponinae): Toxicity and impact of four synthetic insecticides on survival and feeding behavior of stingless bees Tetragonula laeviceps Smith (Hymenoptera: Apidae: Meliponinae) - Bela Hasna Audia; Buchori, Damayanti; Dadang; Raffiudin, Rika (Jurnal Entomologi Indonesia, 2025)
Tetragonula laeviceps Smith are widely found and cultivated in Indonesia. They play a crucial role in providing ecological services as pollinators of plants. However, there has been a global concern of bees’ population decline, which may be attributed to the intensive use of insecticides. This study aimed to analyze the toxicity level of several insecticide active ingredients and the effects of insecticide exposure on the physiology of T. laeviceps. Four insecticides active ingredients, carbosulfan, clothianidin, diafenthiuron, and tetraniliprole were tested for toxicity against T. laeviceps through dermal and oral exposures at five concentration levels. Bee preference testing was conducted through olfactory tests using a Y-tube olfactometer. Results showed that insecticide exposure affected the visitation length of T. laeviceps (P = 0.006), but not its visitation frequency (P = 0.286). Carbosulfan and clothianidin were toxic to T. laeviceps, both dermally (LC50 31.28 and 0.09 ppm, respectively) and orally (LC50 28.51 and 0.41 ppm, respectively). Meanwhile, diafentiuron and tetraniliprole were more harmful to bees during dermal exposure (LC50 7,882 and 148.81 ppm, respectively) compared to oral exposure (LC50 53,983 and 5,240 ppm, respectively). The toxicity levels of the insecticides carbosulfan and clothianidin are classified as highly toxic and harmful, while diafentiuron and tetraniliprole are not harmful to T. laeviceps bees. In addition, the capability of bees to consume feed was also significantly decreased due to exposure to carbosulfan (10,000 and 3,000 ppm) and clothianidin (300; 30; 3; 0,3; and 0,03 ppm) insecticides. Information of the toxicity levels and effects of various insecticides on bees may contribute to the development of insecticide management to keep the survival of bees in agricultural areas.